Physico-Chemical Characteristics of Ice Cream Made from Coconut Milk Cream and Kidney Nut Puree - Sri Winarsih; Nilam Sitaresmi Cahyo; Sukardi Sukardi; Devi Dwi Siskawardani (Food Technology and Halal Science Journal, 2020)
Coconut milk cream is a vegetable fat to replace animal fat in making ice cream. coconut milk cream not having a fishy odor and is rich antioxidants. While kidney nut have the potential as an emulsifier and also rich antioxidants. the purpose of this study was to obtain an optimum formulation of coconut milk and kidney beans to produce ice cream with good characteristics. The study used a simple randomized block design that was repeated three times. The treatment are the proportion of coconut milk cream and kidney nut puree. the results of this study showed that ice cream have moisture 65.79 to 72.61%, 48.99% antioxidant activity, fat content was in accordance with Indonesian national standards (25.32%),overrun value (36.03%) and melting time (8.72 minutes).